Analysis of Added Value and Business Feasibility in Terms of The Economic Aspect of Processing Temurui Leaf Chips (Murraya koenigii) Nusa Village, Lhoknga District - Afta Pratiwi Br Barus; Zakiah; Mustafa Usman (Future Science, 2022)
Temurui or Murraya koenigii, often also called curry leaves or koja greetings, is widely available in Aceh Province which is known in the Acehnese local language